Association between attendance at an American diabetes camp and improvements in glycaemic control and treatment satisfaction. Issue 3 (4th May 2021) - Darukhanavala, Amy; Puhr, Sarah; Dinunno, Kyle; Alfego, David; Welsh, John; Butler, Lynn; Magyar, Kendra
Abstract: Introduction: Few studies have evaluated glycaemic control using continuous glucose monitoring (CGM) in individuals before and after attendance at a diabetes camp or by comparing control groups at home to control groups at camp. Methods: Youth (6–17 years) with T1D and receiving insulin therapy were enrolled at a week‐long diabetes camp. They participated in three clinic visits: at the start of a week at home, by initiating a Dexcom G6 CGM system; at the start of a week at camp, where the home week G6 was removed and a camp week G6 was inserted; and after camp, where the camp week G6 was removed. We administered Problem Areas in Diabetes (PAID) surveys at the second and third visits. Participants with <80% CGM data coverage or who did not complete all PAID surveys were excluded from analysis. We compared glycaemic control and PAID scores between the week at home and week at camp. Results: Of 76 enrolled campers, 69 completed the study and 52 had results that qualified for analysis. The mean participant age was 12.5 ± 2.2 years. Camp was associated with significantly improved treatment satisfaction, time in desired glucose range and insulin sensitivity. Time in hyperglycaemia and basal insulin requirements decreased significantly. Conclusions: Diabetes camp is associated with significant improvements in diabetes treatment satisfaction and glycaemic control compared to home care. Abstract : Children with Type I Diabetes enjoying fun and safe activities at Barton Diabetes Camp. Glycemic control and satisfaction with diabetes improved during camp weeks.